Sistem Pakar Menentukan Gangguan Layanan Indihome Menggunakan Algoritma Best First Search Berbasis Web - al-azizi, khalid mahfudh; akram, rizalul; novianda, novianda (Jurnal Informatika UPGRIS, 2022)
Indihome users are growing rapidly. However, PT Telkom's indihome services are still experiencing various disturbances so that the quality of service is not optimal, with the large number of Indihome users, it is undeniable that there are technicians who understand one type of disturbance better than others and sometimes there are new disturbances that are not understood by many technicians. , technicians who do not understand even those who are familiar with certain disorders may make mistakes in making decisions in dealing with disturbances. This is what prompted the construction of an expert system that aims as a solution to help make it easier for technicians when an interruption occurs in the indihome service, the expert system allows technicians to make consistent decisions to avoid mistakes based on the knowledge of an expert, so that with the solutions provided, technicians are able to take action. what to do when a disturbance occurs and how to deal with the disturbance. The expert system used is the Best First Search algorithm method.